Development of virtual assembly layout with modeling languages approach and simulation using Delmia™ Quest® / Norhidayah Mohamad. - Mohamad, Norhidayah (2011)
The development of virtual model fabrication in this thesis is focusing on manufacturing assembly layout model using modeling languages approach, which are Simulation Control Language (SCL) and Batch Control Language (BCL). SCL is a procedural language in files logic program outlining the development structure of manufacturing layout while the BCL supports the layout by reading the modified model parameters, running the simulation, and providing visual control. This thesis also explores the flexibility of the Layout Data file developed using SCL and BCL approach to drive the Virtual Assembly Layout (VAL) model configurations through simulation and the development process of database for storing and representing the VAL model. The concept and mechanisms of Manufacturing Information (MI) development involves the use of extensible Markup Language (XML). The objectives of the research are therefore to obtain a basic understanding on how these modeling languages are used to develop virtual model and demonstrate the model capability of representing the simulation by using Delmia™ QUEST®. Therefore, it can be concludes that the generated simulation demonstrates the feasibility of interchanging models using modeling language approach as an intermediate representation and provides an opportunity to improve simulation quality.